EMBR-02. OLIG2 REPRESENTS A PROGNOSTIC MARKER AND THERAPEUTIC TARGET IN MYC-AMPLIFIED MEDULLOBLASTOMA RELAPSE AND METASTASIS. (1st June 2021) - Xu, Zhenhua; Murad, Najiba; Rivero-Hinojosa, Samuel; Schüller, Ulrich; Zhang, Peng; Liu, Xiao; Rood, Brian; Packer, Roger; Pei, Yanxin
Abstract: Medulloblastoma (MB) is one of the most common malignant pediatric brain tumors. Among the multiple MB subtypes, MB with MYC amplification confers an extremely poor prognosis with an overall survival rate of less than 30%. Relapse is often mediated by a small population of therapy-resistant tumor cells which expand and ultimately progress to lethal tumors. Moreover, MYC -amplified MB exhibits a high incidence of leptomeningeal metastases. Approximately one-third of patients with MYC -amplified MB present with metastases and nearly all have this complication at relapse. Metastatic MYC -amplified MB is highly fatal. As such, our ability to effectively treat MYC -amplified MB is largely dependent on our capacity to eradicate the therapy resistant tumor cells, particularly the metastatic tumor cells. The development of clinically effective therapies for this disease will be facilitated by the identification of therapy-resistant tumor cell populations and their molecular signatures involved in tumor metastasis and relapse. Using patient-derived xenograft (PDX) mouse models, we recently discovered that a subset of MYC -amplified MB tumors with strong OLIG2 expression (OLIG2 -high ) is resistant to radiation and prone to metastasize, whereas MYC -amplified MB tumors without OLIG2 expression (OLIG2 -low ) are sensitive to radiation without dissemination. Irradiation of OLIG2 -high tumors led to either a small number of quiescent OLIG2 - cancer stem-like cells (CSLCs) remaining in the cerebellar bed or to the dissemination of highly proliferative OLIG2 + tumor cells along the leptomeninges. All mice harboring these radioresistant CSLCs succumbed to relapse. Further studies demonstrated that the quiescent OLIG2 - CSLCs did not contribute to tumor recurrence directly, while elimination of OLIG2 + radioresistant CSLCs with a small molecule OLIG2 antagonist significantly prevented metastatic recurrence, delayed tumor growth and prolonged animal survival. Thus, our studies provide new insights into the role of OLIG2 in radiotherapy resistance and metastasis in MYC -amplified MB and propose a novel therapeutic approach to treating metastatic MYC -amplified MB.